Oral health status in patients with epilepsy - Shamsolmoulouk Najafi; Soheila Manifar; Abbas Tafakhori; Sudabe Heydari; Mina Khayamzadeh; Mohammad Javad Kharazi Fard (Journal of Craniomaxillofacial Research, 2018)
Introduction: Epilepsy is one of the most common chronic neurologic diseases. It has a great influence on quality of life, as it engages 1-3% of a society. Normally, 10% of the people of the society have experienced seizure once or several times during their lives. Regardingalldentistry aspects, they receive insufficient treatments, which might be due to the medical and economic status of them. Oral health is of paramount importance. Objective: This research aims at examining oral health status of the patients with epilepsy, comparing them with the non-patient ones from systemic point of view, and evaluating periodontal treatment needs. Materials and Methods: Sixty patients were randomly includedin this cross-sectional study. They were divided into 2 subgroups of partial and general (based on frequencies of seizures, type of seizure, and mental status). Sixty systemically non-patient people who referred to the Imam Khomeini Hospital for blood donation were randomly included in the study as the control group. They were medical and epilepsy history. Oral examinations were carried out. The Simplified Oral Hygiene Index (OHI-S), decay-missing-filled tooth (DMF-T), normal teeth abrasion rate (Abrasion Index), Prosthetic Index; periodontal treatment needs (CPITN) and Muhleman index were evaluated and a statistical comparison was made between the patient group and the control group and between the epilepsy subgroups. Results: OHI-S index, DMF-T index, Muhlemman index and Prosthetic index of the patient group was considerably higher than the one of the control group. About CPITN index, In mandible, the patient group has a significant difference with the control group, except in the area of the second left molar. Conclusion: Several factors contributed to worsening oral health status in the patient group as compared with the control group. For example, the effect of seizure itself, negative attitudes of dentists, and social and economic conditions. We propose to start oral treatments concurrent with the  treatments concerning epilepsy. Some special dental interventions were proposed for each subgroup. Keywords: Epilepsy, Oral healt, Periodontal.